2020
DOI: 10.1098/rsbl.2020.0281
|View full text |Cite
|
Sign up to set email alerts
|

Fingers zipped up or baby mittens? Two main tetrapod strategies to return to the sea

Abstract: The application of network methodology in anatomical structures offers new insights on the connectivity pattern of skull bones, skeletal elements and their muscles. Anatomical networks helped to improve our understanding of the water-to-land transition and how the pectoral fins were transformed into limbs via their modular disintegration. Here, we apply the same methodology to tetrapods secondarily adapted to the marine environment. We find that these animals achieved their return to the sea with four types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…Future studies should address whether other lineages with relatively big brains, such as dolphins within cetaceans (Marino, 2009) or corvids within birds (Uomini et al, 2020), convergently evolved a similar relationship between cranial anatomy and brain size. On a more general note, the results presented here add up to a growing body of research that seeks to better understand morphological evolution, development, and function by using methods that allow us to studying the body's anatomy as a complex biological system (Esteve-Altava et al, 2013, 2019Saucède et al, 2015;Dos Santos et al, 2017;Kerkman et al, 2018;Murphy et al, 2018;Werneburg et al, 2019;Fernández et al, 2020;Plateau & Foth, 2020;Sookias et al, 2020).…”
Section: Discussionmentioning
confidence: 87%
“…Future studies should address whether other lineages with relatively big brains, such as dolphins within cetaceans (Marino, 2009) or corvids within birds (Uomini et al, 2020), convergently evolved a similar relationship between cranial anatomy and brain size. On a more general note, the results presented here add up to a growing body of research that seeks to better understand morphological evolution, development, and function by using methods that allow us to studying the body's anatomy as a complex biological system (Esteve-Altava et al, 2013, 2019Saucède et al, 2015;Dos Santos et al, 2017;Kerkman et al, 2018;Murphy et al, 2018;Werneburg et al, 2019;Fernández et al, 2020;Plateau & Foth, 2020;Sookias et al, 2020).…”
Section: Discussionmentioning
confidence: 87%
“…Following Esteve‐Altava et al (2019) and Fernández et al (2020), different parameters from each network were obtained using the R package Igraph (Csardi & Nepusz, 2006): (1) number of nodes ( N ); (2) number of links ( L ); (3) density ( D ), which is a measure of how close is the network to be a complete graph, and is obtained by dividing the number of links by the number of maximum possible links in the network; (4) average cluster coefficient (ACC), which is the average of the local cluster coefficient, a measure of each node related to the connectivity of the adjacent nodes; (5) average shortest path length (APL), which is the average length of all shortest or geodesic paths (i.e., the minimal number of links connecting every two nodes) in a network; (6) heterogeneity ( H ), which is a measure of how even are the nodes according to their number of connections; (7) average degree (AD), which is the average number of links of each node; (8) network diameter (ND), which is the length of the longest geodesic path; and (9) modularity ( Q ). Modularity was calculated by dividing all the networks in different communities using the algorithm clustering walktrap, which detects communities by short random walks, as random walks in a graph tend to be trapped into densely connected subgraphs (Pons & Latapy, 2005); then the resulting membership structure was used to calculate Q (Newman & Girvan, 2004).…”
Section: Methodsmentioning
confidence: 96%
“…Following Esteve-Altava et al ( 2019) and Fernández et al (2020), different parameters from each network were obtained using the R package Igraph (Csardi & Nepusz, 2006): (1) number of nodes (N);…”
Section: Network Analysismentioning
confidence: 99%
“…(2018) , Esteve-Altava et al. (2019) , and Esteve-Altava & Rasskin-Gutman (2014) ; Parcellation was calculated as in Fernández et al (2020) . Our data are summarized in Table 1 ; see supplemental information as well.…”
Section: Methodsmentioning
confidence: 99%
“…The solid theoretical foundations of the AnNA ( Esteve-Altava, 2013 ; Rasskin-Gutman & Esteve-Altava, 2014 ) has allowed its successful application in various anatomical structures, like the mammalian skeleton ( Powell et al, 2018 ), tetrapod skull ( e.g. , Esteve-Altava et al, 2013a ; Esteve-Altava et al., 2013b ; Esteve-Altava & Rasskin-Gutman, 2014 ; Lee, Esteve-Altava & Abzhanov, 2020 ) and tetrapod limbs ( Molnar et al, 2017 ; Esteve-Altava et al, 2018 ; Esteve-Altava et al, 2019 ; Fernández et al, 2020 ), among many other studies. In particular, a recent AnNA analysis of 44 tetrapod skulls by Esteve-Altava et al (2013a) revealed that the reduction in the number of skull bones during tetrapod evolution increased the complexity of the connectivity pattern under a regime of important structural constraints.…”
Section: Introductionmentioning
confidence: 99%